2016
DOI: 10.1128/jvi.01624-16
|View full text |Cite
|
Sign up to set email alerts
|

Role of LAMP1 Binding and pH Sensing by the Spike Complex of Lassa Virus

Abstract: To effectively infect cells, Lassa virus needs to switch in an endosomal compartment from its primary receptor, ␣-dystroglycan, to a protein termed LAMP1. A unique histidine triad on the surface of the receptor-binding domain from the glycoprotein spike complex of Lassa virus is important for LAMP1 binding. Here we investigate mutated spikes that have an impaired ability to interact with LAMP1 and show that although LAMP1 is important for efficient infectivity, it is not required for spike-mediated membrane fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 28 publications
13
85
0
Order By: Relevance
“…Recent electron cryotomography studies on authentic LASV particles revealed conformational changes in GP1 to occur under pH 5, in line with the X-ray data (66). Although LAMP1 is crucial for productive LASV entry (64), LAMP1 binding is not strictly required for fusion per se, evidenced by mutations within the histidine triad that were still able to undergo fusion, albeit at lower pH (67). Elegant functional studies demonstrated that residue H230 within the histidine triad on LASV GP1 undergoes protonation around pH 5.5, when GP1 starts dissociating from DG (Fig.…”
Section: Lamp1 Is a Late Endosomal Entry Factor For Lasv That Facilitmentioning
confidence: 66%
“…Recent electron cryotomography studies on authentic LASV particles revealed conformational changes in GP1 to occur under pH 5, in line with the X-ray data (66). Although LAMP1 is crucial for productive LASV entry (64), LAMP1 binding is not strictly required for fusion per se, evidenced by mutations within the histidine triad that were still able to undergo fusion, albeit at lower pH (67). Elegant functional studies demonstrated that residue H230 within the histidine triad on LASV GP1 undergoes protonation around pH 5.5, when GP1 starts dissociating from DG (Fig.…”
Section: Lamp1 Is a Late Endosomal Entry Factor For Lasv That Facilitmentioning
confidence: 66%
“…7A). Previous work by Cohen-Dvashi et al tested Fusion activity individual mutations H92Y, H93Y, and H230Y for processing, surface expression, and fusion activity (30). When they individually changed each histidine to tyrosine, they found a reduction in the level of cleaved, surface-expressed GP but no significant changes in cell-cell fusion.…”
Section: Additional Targeted Mutationsmentioning
confidence: 99%
“…The transduction defect in HAP1 cells with no defect in HAP1 ΔDAG1 cells suggests that F147 is important for efficient ␣DG utilization. Fourteen conserved charged residues were mutated to alanine, including a described histidine triad (H92, H93, and H230), which has been implicated in LAMP1 interaction (30,33). All mutated GPs were cleaved and transported to the cell membrane at levels greater than 60% of parental GP (Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of LAMP1 is driven by a triad of histidines on the GP1 and that binding of LAMP1 triggers the LASV spike to catalyze membrane fusion by potentiating its response to pH [29,48]. While this histidine triad is conserved among other OW arenaviruses, LAMP-1 utilization has been shown to be specific for LASV, and LAMP1 is not utilized by LCMV or other OW arenaviruses, regardless of α-DG affinity [27,49].…”
Section: The Arenavirus Life Cyclementioning
confidence: 99%